The analysis of telecom operator’s revenue dependence on different routing and interconnection charging methods - Kostić-Ljubisavljević, Aleksandra; Mladenović, Snežana; Aćimović-Raspopović, Vladanka (Technological and Economic Development of Economy, 2012)
Telecommunication operators endeavour to offer their users numerous services and, at the same time, to be competitive with other operators at the market while accomplishing high revenue. The only way to achieve all those goals is to make better usage of their network resources and realise high network efficiency. In this paper, we tested the assumption that a proper combination of the different dynamic telecommunication traffic routing methods and interconnection charging methods can provide higher operators revenue. In order to analyze the effects of combinations of four different routing and two interconnection charging methods on operator’s revenue, we developed new software for simulation of network operations. This software is used for simulation of the three interconnected networks operators. Results considering the dependence of operator’s revenue on routing and interconnection charging methods combination are analyzed and discussed.